Evaluation of the effect of Ramadan fasting on fat-soluble antioxidants and markers of oxidative stress in healthy Pakistani subjects. Issue 4 (25th February 2017) - Khan, Abad; Iqbal, Zafar
ABSTRACT: The aim of this study is to evaluate the effect of Ramadan fasting on the fat-soluble antioxidants [all- trans -retinol (vitamin A) and α -tocopherol (vitamin E)] in healthy Pakistani subjects. Thirty (30) healthy male volunteers (aged 30–50 years) with Ramadan fasting have participated in the study. Blood sampling from these subjects was conducted 1 day before and on 15th and 28th days of Ramadan. The serum levels of vitamin A and vitamin E were measured using liquid chromatography linked with UV–visible (HPLC–UV). The comparison between the samples taken at different times was made by Minitab software applying two samples and paired t -test at ( p  < 0.05) as significant. No significant changes have been found in the levels of all- trans -retinol before and during Ramadan values. The levels of α -tocopherol on 28th Ramadan have been decreased significantly when compared with its values before Ramadan ( p  < 0.0001). It is concluded that there is nonsignificant change in the levels of vitamin A during the month of Ramadan while the levels of α -tocopherol have been decreased significantly on the 28th day of Ramadan. It is therefore suggested that the fasting of Ramadan has effect on the levels of α -tocopherol and food-based interventions might be necessary to modify the diet during Ramadan. GRAPHICAL ABSTRACT: